2019
DOI: 10.4236/tel.2019.92026
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Online Travel Adoption Intention of an Indian Consumer: A SEM-Neural Network Approach

Abstract: Online channel has redefined the way businesses were conducted and many e-travel firms were the first to exemplify. The purpose of this paper is to determine the key factors that influence consumers' intention to adopt online channel for train travel. The extended model incorporates the basic ingredients of TAM, TPB and Shim's model along with several external variables such as trust, convenience and involvement. Data were collected from 514 online travel customers. In the first phase, structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Although the findings related to trust is consistent with previous studies (Gefen et al. , 2003; Koundinya, 2019), the most interesting and novel finding of this study, different from previous studies, is that trust was found the most important and the strongest factor to influence consumer’s intention than attitude and subjective norms. The reason for this could be that during COVID-19, trust was the major concern while ordering food and beverage items.…”
Section: Discussionsupporting
confidence: 80%
“…Although the findings related to trust is consistent with previous studies (Gefen et al. , 2003; Koundinya, 2019), the most interesting and novel finding of this study, different from previous studies, is that trust was found the most important and the strongest factor to influence consumer’s intention than attitude and subjective norms. The reason for this could be that during COVID-19, trust was the major concern while ordering food and beverage items.…”
Section: Discussionsupporting
confidence: 80%
“…Further, we found that the behavioral intention to use digital public services is directly and favorably affected by perceived trust. This result supports Hypothesis H8, which is consistent with earlier research (e.g., Alzoubi et al 2019;Bélanger and Carter 2008;Chatzoglou et al 2015;Gu et al 2009;Koundinya 2019;Kumar and Sachan 2017;Voutinioti 2013;Zahid and Din 2019;Zeebaree et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Subjective norms indicate social influence which encourages or discourages people to perform a particular behavior (Rivis et al, 2009;Bae and Chang, 2020). It is explained as traveler's perception of social normative pressures created by friends, family, peers and others' beliefs (Taylor and Todd, 1995;Koundinya, 2019) and social influence is the perception held by travelers of what others who are important to them, think their traveling behavior should be like (Fishbein and Ajzen, 1975;Koundinya, 2019). Subjective norm is a predictor of behavioral intention in the TPB, which influences behavior.…”
Section: Subjective Normsmentioning
confidence: 99%